Damage Level Determination of Mango on Simulation Transport Position, Operated on Various Vibration - Nugroho, Wahyunanto Agung; Lutfi, Musthofa; Prasetyo, Dedy Dwi (Jurnal Teknologi Pertanian, 2011)
The objective of this research is to know the influence of vibration on the physical condition of the fruit as well as to determine the best position of mangoes during transportation. The method used in this research was by performing physical tests of mangoes using a transportation simulation process. The benefit of this research is finding the most effective way to reduce damage during transportation. Â This research was using the experimental method with two treatment; i.e. vibration in three levels (2, 3 and 4 cm) and mangoes position as well. The physical condition analysis was emphasized on the fruit pressure value. The result was indicated the significant different between the fruit pressure value before and after transport simulation. The biggest value is vertical position with the former stem below (Va). However, there are no significant difference between upper layer and bellow layer of fruit position.Keywords: gadung mango, physical damage, transport position, vibration